Relationships between reaction time, sprint race result and age for male sprinters at 2004 Olympic Games in Athens - Babic, V.; Mitrovic, T.; Delalija, A. (World Congress of Performance Analysis of Sport VIII, 2008)
In conclusion, it can be said that reaction time has significant influence on sprint result but only in short sprint events. It is also evident that there are significant differences in reaction time between shorter and longer sprint events. Sprint event 200 m flat is useful in demonstrating how with increment of sprint event distance the significance of reaction time becomes less relevant. When it comes to reaction time, it is interesting how top-level sprinters do not show significantly better values of reaction time than sprinters who managed to perform in qualification and semifinals rounds. Furthermore, it can be ascertained that athletes performing in decathlon events do not fall behind the sprinters of "regular" sprint events in their reaction time values. It was found that older sprinters tend to react faster at the start. That means that in training preparation with younger sprinters more attention should be devoted to psychological preparation.